2021
DOI: 10.1002/cbic.202100092
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time and Label‐Free Measurement of Deubiquitinase Activity with a MspA Nanopore

Abstract: Covalently attaching ubiquitin (Ub) to cellular proteins as a post-translational modification can result in altered function of modified proteins. Enzymes regulating Ub as a post-translational modification, such as ligases and deubiquitinases, are challenging to characterize in part due to the low throughput of in-vitro assays. Single-molecule nanopore based assays have the advantage of detecting proteins with high specificity and resolution, and in a label-free, real-time fashion. Here we demonstrate the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Recently, the large vestibule of Mycobacterium smegmatis porin A (MspA) has been applied as a nanopore trap to probe protein activities of calmodulin and deubiquitinase. , A recent report also demonstrates that nucleic acid translocation through an α-HL and MspA was retarded in the presence of a calcium flux. , Thus, we further applied this asymmetric electrolyte combination to the MspA nanopore trap for protein structural profiling. The accumulated multivalent cations bound tightly to the negatively charged pore lumen were expected to switch the effective surface charge and to trigger the generation of EOF in nanopores.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the large vestibule of Mycobacterium smegmatis porin A (MspA) has been applied as a nanopore trap to probe protein activities of calmodulin and deubiquitinase. , A recent report also demonstrates that nucleic acid translocation through an α-HL and MspA was retarded in the presence of a calcium flux. , Thus, we further applied this asymmetric electrolyte combination to the MspA nanopore trap for protein structural profiling. The accumulated multivalent cations bound tightly to the negatively charged pore lumen were expected to switch the effective surface charge and to trigger the generation of EOF in nanopores.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier attempts to investigate proteins bearing a PTM were also made. We and others showed that unmodified and ubiquitinated proteins have a different signal, which could be used to follow the ubiquitination reaction . It was also reported that nanopores functionalized with an antibody can distinguish between its cognate glycosylated or unglycosylated protein .…”
Section: Detection Of Glycopeptides Using Fracmentioning
confidence: 99%
“…[43][44][45][46] Unlike classic nanopore analysis which measures the current fluctuations induced by analytes transiently traversing the nanopore, nanopore tweezers work by confining a single analyte molecule within its lumen to continuously record ionic current fluctuations associated with the analyte's motions in real time. 44,[47][48][49][50][51] Cytolysin A (ClyA), a pore-forming protein in enterobacterial species including Escherichia coli (E. coli) and Salmonella typhi (S. typhi), 52 has been developed as a nanopore tweezers for studying the ligand binding of multiple substrate-binding proteins, 49 resolving the conformational energy landscape of a pharmaceutically important protein, Abl kinase domain, and detecting the inhibitor imatinib binding. 44 To select molecules which stabilize the inhibitory open conformations, it is necessary to establish an approach capable of observing the open and closed conformations in NS2B/NS3.…”
Section: Introductionmentioning
confidence: 99%